TINJAUAN YURIDIS TERHADAP PERLINDUNGAN HAK CIPTA DALAM PENGGUNAAN KARYA CIPTA MUSIK DAN LAGU KARAOKE - Agus Dimyati (Hukum Responsif, 2015)
ABSTRACTThe right to copyright is automatic, ie once a creature is born or after the manifestation of an idea into a tangible form without requiring a certain formality, unlike industrial property rights, the emergence of the right to be with a certain formality that is music or songs that have been created someone. Relate in fact, very well be required for the protection of creative works of music and song therefore it is necessary to know more about the application of the provisions of the Copyright protection Copyright particularly concerning copyrighted works of music and song in the house karaoke businesses as well as the license is required as a contract. The license must be realized in the form of a contract, therefore each party has the right to set things he wanted.            The method used is normatf juridical approach, meaning an approach which is done by examining the secondary data or library materials. The research method is descriptive method of analysis done, which describes the protection of Copyright in the use of copyrighted works of music and song. Data used in the study include, namely primary data by means of direct interview to the informant mapun indirectly related to research studies ang secondary data namely review of literature or Library Research.            Based on this research, iti turns out that not all of this license agreement is made in a letter written agreement or deed, such agreements generally. System agreement with a deed to the agreement, only used by the creators who already have a name and often a song litle track. For creators who wa unknown or they are new, usually just wear receipt receipt only. Legal protection given to the rights of the creator or copyright holder in the license agreement on the implementation of this song is basing the existing provisions in the Act Copyright Act No. 28 Year 2014.            Keywords : Copyright, Music, Lissenced.